Society and Technology: Promoting Public Awareness in the VUCA World Characterized by Disruption (Universitas Terbuka, 2023)
This paper examines the association between society and technology in the context of a volatile, uncertain, complex, and ambiguous (VUCA) environment characterized by disruption. The study mainly focuses on promoting public awareness of the impact, challenges, and opportunities arising from the intersection of society and technology. Through a qualitative research approach. i.e., combining a systematic literature review and a comprehensive literature review, the study then analyzes the meaning and interplay between society and technology, explores the dynamics of public awareness in the VUCA and disruption context, and proposes processes and procedures to effectively promote public awareness in linking society and technology. The study, therefore, aims at (1) contributing a better understanding of the critical role public awareness plays in navigating the challenges of a rapidly evolving technological landscape and (2) fostering informed decision-making for proper choices in a VUCA world in accordance with Megatrends toward 2030. The study finally shows that technology has become an integral part of our lives. It influences various aspects such as communication, education, healthcare, and the economy. At the same time, public awareness helps individuals understand the nature of disruption, anticipate potential challenges, and identify opportunities to acquire the necessary knowledge and skills to thrive in a VUCA environment.